Anxiety, depressiveness and irritability in parents of children treated surgically for congenital heart defects - Składzień, Tomasz; Górecka, Katarzyna; Wiśniowski, Zdzisław; Jaworska, Izabela; Wójcik, Elżbieta; Mroczek, Tomasz; Skalski, Janusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Introduction : A diagnosis of congenital heart disease (CHD) in children is a major psychological stress for their parents. Aim of the study : The aim of this study was to determine parents’ emotional response to the surgery and changes to the intensity of parents’ negative emotions before and after the surgery. Material and method : The study included 65 parents (54 mothers and 11 fathers) of children treated at the Department of Pediatric Cardiac Surgery, Polish-American Institute of Pediatrics, the Jagiellonian University in Cracow in 2010. We used a modified scale of HADS (Hospital Anxiety and Depression Scale) to assess parents’ emotional reactions. It examines the level of anxiety, depression and aggression (irritability), according to Snaith and Zigmond which has been modified into the Polish version by Majkowicz, de Walden-Gałuszko and Chojnacka-Szawłowska. Results: A fear before the surgery was diagnosed among 51 (78.5%) parents, and 4 weeks after the surgery among 6 (9.2%) parents. The depression was diagnosed among 22 (33.8%) parents before the surgery, and only one mother (1.5%) had it after leaving the hospital. The increased irritability (aggression scale) was observed among 28 (43%) parents, and 9 (13.8%) parents had elevated levels of aggression after hospital discharge. Conclusions : The diagnosis of congenital heart disease is taking its toll on the functioning of families of children undergoing operation, despite the withdrawal symptoms of stress associated with the surgery. It is reasonable to support psychologically such families from the time of preparation for the surgery, and educate parents about children’s health and support them after leaving the hospital in order to reduce a long-term mental stress associated with the diagnosis of congenital heart defects among children.